Upaya Strategik Penguatan Kompetensi Guru di SD Negeri 4 Krandegan Banjarnegara - Atut Sugiarti; Hartono Hartono; Nurhasanah Nurhasanah (Jurnal Kependidikan, 2021)
This study aimed to: (1) analyze the competence of teachers at SD Negeri 4 Krandegan, Banjarnegara District, Banjarnegara Regency; (2) analyzing the strategic efforts to strengthen teacher competence in SD Negeri 4 Krandegan, Banjarnegara District, Banjarnegara Regency. This research method uses descriptive quantitative and qualitative descriptive research. Data collection techniques in the form of questionnaires, interviews, observations and documentation studies. While the data analysis technique uses data reduction, data presentation, and drawing conclusions. The results showed that the competence of teachers at SD Negeri 4 Krandelan was very good. The strategic efforts to strengthen competence were carried out, namely: (1) pedagogic competence: by discussing with teachers both formal and non-formal, giving assignments to teachers to transmit the results of technical guidance, holding workshops, supervision, comparative studies, increasing time allocation; (2) personality competencies: giving rewards, freedom of opinion, coaching, and bringing in lecturers; (3) Professional competence: facilitating teachers to be active in the KKG, increasing teacher insight, encouraging teachers to take part in scientific/innovative work competitions, assigning tasks to teachers to guide academic competitions, assigning teachers to guide and develop curriculum development, involving teachers to become curriculum development teams in schools ; (4) Social competence: design learning with cooperative methods, group activities that require collaboration, such as outbound, extracurricular, tourism, being friends in CAR, and giving dispensation to teachers in community activities.